Transfer of students' learning about x-rays and computer-assisted tomography from physics to medical imaging - Kalita, Spartak A. (Kansas State University, 2008)
In this study we explored students' transfer of learning in the X-ray medical imaging context, including the X-ray-based computer-assisted tomography (or CAT). For this purpose we have conducted a series of clinical and teaching interviews. The investigation was a part of a bigger research effort to design teaching-learning materials for pre-medical students who are completing their algebra-based physics course. Our students brought to the discussion pieces of knowledge transferred from very different sources such as their own X-ray experiences, previous learning and the mass media. This transfer seems to result in more or less firm mental models, although often not internally consistent or coherent. Based on our research on pre-med students' models of X-rays we designed a hands-on lab using semi-transparent Lego bricks to model CAT scans. Without "surgery" (i.e. without intrusion into the Lego "body") students determined the shape of an object, which was built out of opaque and translucent Lego bricks and hidden from view. A source of light and a detector were provided upon request. Using a learning cycle format, we introduced CAT scans after students successfully have completed this task. By comparing students' ideas before and after teaching interview with the groups of 2 or 3 participants, we have investigated transfer of learning from basic physics and everyday experience to a complex medical technology and how their peer interactions trigger and facilitate this process. During the last phase of our research we also introduced a CAT-scan simulation problem into our teaching interview routine and compared students' perception of this simulation and their perception of the hands-on activity.
Keywords: physics education; X-rays; CAT-scans; mental models; transfer of learning; medical physics; Physics, Radiation (0756)